EVALUASI TINGKAT PENERIMAAN DAN PENGGUNAAN APLIKASI PEDULILINDUNGI MENGGUNAKAN MODEL UTAUT 2 - Nuraini Azizi Rachim (2021)
PeduliLindungi is a COVID-19 pandemic surveillance system that can be evaluated using the UTAUT 2 (Unified Theory of Acceptance and Use of Technology 2) model. In this research, Behavioral Intentions and Use Behavior were measured by constructs of Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, and Habit. The results of this research are Path Coefficient and T-Statistics values for the effect of Effort Expectancy on Behavioral Intentions are 0.024 and 0.501, Social Influence on Behavioral Intentions are 0.033 and 0.678, Facilitating Conditions on Behavioral Intentions are 0.016 and 0.377, and Facilitating Conditions on Use Behavior are 0.024 and 0.608, which is less significant. While Path Coefficient and T-Statistics values for Performance Expectancy on Behavioral Intentions are 0.257 and 4.204, Hedonic Motivation on Behavioral Intentions are 0.177 and 2,935, Habits on Behavioral Intentions are 0.413 and 6.835, Habits on Use Behavior are 0.564 and 9,461, and Behavioral Intentions on User Behavior are 0.127 and 2.150. The performance of the application is good, users are satisfied and accustomed to use PeduliLindungi. However, the ease of use need to be improved, socializing the use of the application, and there are still many people who do not have adequate devices.